Revaluation of Student Failure Reasons Using Non-Additive Methods (Baghdad Science Journal, 2025)
In this paper, An application of non-additive measures for re-evaluating the degree of importance of some student failure reasons has been discussed. We apply non-additive fuzzy integral model (Sugeno, Shilkret and Choquet) integrals for some expected factors which effect student examination performance for different students' cases.